Methotrexate treatment of FraX fibroblasts results in FMR1 transcription but not in detectable FMR1 protein levels - Brendel, Cornelia (BioMed Central, 2013)
BACKGROUND: Fragile X syndrome is caused by the loss of FMRP expression due to methylation of the FMR1 promoter. Treatment of fragile X syndrome patients’ lymphoblastoid cells with 5-azadeoxycytidine results in demethylation of the promoter and reactivation of the gene. The aim of the study was to analyze if methotrexate, an agent which also reduces DNA methylation but with less toxicity than 5-azadeoxycytidine, has therapeutic potential in fragile X syndrome. METHODS: Fibroblasts of fragile X syndrome patients were treated with methotrexate in concentrations ranging from 1 to 4 μg/ml for up to 14 days. FMR1 and FMRP expression were analyzed by quantitative PCR and western blotting. RESULTS: FMR1 mRNA was detected and levels correlated positively with methotrexate concentrations and time of treatment, but western blotting did not show detectable FMRP levels. CONCLUSIONS: We show that it is possible to reactivate FMR1 transcription in fibroblasts of fragile X syndrome patients by treatment with methotrexate. However, we were not able to show FMRP expression, possibly due to the reduced translation efficacy caused by the triplet repeat extension. Unless FMR1 reactivation is more effective in vivo our results indicate that methotrexate has no role in the treatment of fragile X syndrome.